(untitled) (Cultura Económica, 2019)
In this paper, the author proposes to reflect on some aspects of the book The Idea of Justice by Amartya Sen, in the light of the work of the Italian philosopher Antonio Rosmini, disseminator of the term “social justice” in the origins of Catholic social thought. First, the author shows the similarities between Sen and Rosmini on the importance of reason in the analysis of the idea of social justice against purely emotional and pragmatic proposals. Secondly, he proposes a comparison between the critiques developed by Sen and Rosmini to the so-called by Sen “transcendental theories” of justice and the so-called “structural changes” and the need for gradual changes to reach a just society. Thirdly, the paper intends to show how the choice for the people and their capabilities taken by Sen can be enlightened and deepened from the perspective of the Rosminian theory of capabilities. Then, it describes the cognitive turn proposed by Sen for institutions and public policies. Finally, the author enounces some objections that could be made to the pose suggested in the paper, along with some final comments about them.